The poetics and politics of Englishes in late modernity. Issue 1 (3rd June 2019) - Bhatt, Rakesh M.
Abstract: This paper argues that the 'liberation linguistics' perspective that Professor Kachru championed achieved two important aims: (i) it explored the creative manipulation of multilinguals' repertoire in the late‐modern contexts of mobility and complexity; and (ii) it brought into focus the sociolinguistic inequalities engendered by a politics of conformity. Braj Kachru's teaching consistently highlighted the heterogeneity and multifunctionality of language, together with the meaning potential of variation, and his work continues to provide inspiration for the ongoing development of the field, and the 'gloriously impure' alchemy of English that he has bequeathed to us all.